Cure kinetics of epoxy systems modified with block copolymers - Larranaga, M. (2004)
The kinetics pathway of a 4,4′‐diaminodiphenylmethane‐cured diglycidyl ether of bisphenol‐A (DGEBA) epoxy system modified with a PEO–PPO–PEO block copolymer has been investigated by differential scanning calorimetry. The curing progress of this system has also been studied by dielectric relaxation spectrometry following changes in the main α‐relaxation. An interesting finding is the change in rate constant with copolymer content. Infrared spectroscopy shows that this change is due to interactions between the hydroxyl groups of the growing epoxy thermoset and the ether bonds of the block copolymer. The proposed phenomenological autocatalytic model provides a good description of the cure behaviour of this epoxy/copolymer system for all cure cycles used.